Moral Disengagement Dan Locus Of Control Sebagai Prediktor Agresivitas Narapidana Di Lapas Kelas IIB Muara Enim - Setiawan, Ari; Aulia, Qisthina (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to determine the influence of moral disengagement and locus of control on the aggressive behaviour of repeat offenders at the Muara Enim Class IIB Correctional Institution. The background of this study is the high incidence of aggression within correctional institutions, which is thought to be influenced by certain psychological factors, particularly how individuals view moral values and their perception of self-control. The research approach used is quantitative, using a survey method. The population in this study consists of all repeat offenders at the Muara Enim Class IIB Correctional Institution, and the sample was selected using purposive sampling. The data collection instrument is a questionnaire measuring three variables: moral disengagement, locus of control, and aggressive behaviour, which have been tested for validity and reliability. Data analysis techniques used multiple linear regression with the assistance of the SPSS program. The results of the study indicate that, partially, moral disengagement has a significant positive influence on the aggressive behaviour of prisoners, as does locus of control. Simultaneously, both variables together also show a significant influence on aggression. This study yielded an R value of 0.825 and an R Square of 0.680, with a significance level of p = 0.000 (<0.05) and the multiple regression equation Y = 78.379 + 0.473 X1 + -0.706 X2. These findings indicate that prisoners who tend to disengage from moral responsibility and have an external locus of control are more likely to exhibit aggressive behaviour during their prison term. The higher the level of Moral Disengagement, the more aggressive the prisoners' behaviour becomes, and conversely, the lower the level of Moral Disengagement, the less aggressive the prisoners' behaviour becomes. The higher the level of locus of control, the more aggressive the prisoners' behaviour will be, and conversely, the lower the level of locus of control, the less aggressive the prisoners' behaviour will be.